INFLUENCE OF HOMEOSTATIC CYTOKINES – IL-7 AND IL-15 ON T-REGULATORY CELLS IN VITRO - D. V. Shevyrev; V. A. Kozlov (Медицинская иммунология, 2021)
Cytokines IL-7 and IL-15 are the most important humoral factors providing T-conventional cell pool reconstitution during homeostatic proliferation caused by lymphopenia. However, whether these cytokines can provide homeostatic maintenance and proliferation of T-regulatory (Treg) cells is largely unknown. Considering the association between homeostatic proliferation and the development of autoimmunity, we decided to investigate the ability of these factors to cause differentiation of Treg-cells into Th17-lymphocytes. Therefore, the purpose of this study was to investigate the influence of humoral factors of homeostatic proliferation (IL-7 and IL-15) on Treg-cells in vitro. The study used peripheral blood sampled from 22 healthy donors. PBMC fraction was isolated by Ficoll density gradient centrifugation. Proliferation was induced by IL-7, IL-15, and by a combination of IL-2 with anti-CD3-antibodies. The proliferation intensity of Tregs was evaluated by flow cytometry using CFSE in PBMC cultures by phenotype CD3+CD4+CD25+FoxP3+ and in the previously purified population of CD3+CD4+CD25+CD127lo-cells. In this case Treg-cells were obtained by immunomagnetic separation from PBMCs using a MACS Treg Isolation Kit. Also, the RORyt expression in CD3+CD4+CD25+FoxP3+-cells was evaluated during cultivation. Here, we have shown that IL-7 and IL-15 could support Treg-cells by number and phenotype. Also, we revealed that these factors provide FoxP3 expression in Treg-cells; meanwhile, stimulation with IL-2 + anti-CD3 can also cause induction of FoxP3 expression de novo in conventional CD4+ cells. Also, we have shown that IL-7 and IL-15 can cause lower-intensity proliferation of Treg-cells in comparison with IL-2 + anti-CD3. Herewith homeostatic cytokines didn’t have the ability to induce RORyt expression in both T-regulatory cells and CD4+ conventional T-lymphocytes. Thus, it has been shown that IL-7 and IL-15 can potentially participate in maintaining the total pool of Treg-cells during lymphopenia, when IL-2 deficiency occurs, without causing the induction of RORyt expression. However, how homeostatic cytokines affect the functional activity of Treg-cells remains unclear and requires further investigation.